Comparsion of Outcomes (Maternal and Foetal) in Obese and Non-Obese Pregnant Women - Shazia Tabassum, Nasreen Kishwar, Shabnum Jaffri, Shazia Anwar, Mohammed Alorini, Iffat Imran, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this research is to compare the risk factors for unfavorable pregnancy outcomes between obese and non-obese women. Study Design: Randomized controlled trial Place and Duration: Hayatabad Medical Complex Peshawar, during from the period Jan, 2021 To June, 2021. Methods: In all, 130 participants signed up to take part in this research. The ages of the patients ranged from 18 to 42 years. A total of 65 patients who were obese (BMI>25kg/m3) were enrolled in group M, while an equal number of patients who were non-obese (BMI <25kg/m2) were included in group N. We compared the adverse events that occurred in both groups with regard to the outcomes for the mother and the baby. SPSS 21.0 was used to perform an in-depth analysis on all of the data. Results: We found that frequency of pre-eclampsia, gestational diabetes mellitus and post-partum haemorrhage post-partum hemorrhage was higher in obese group than that of non-obese patients. Frequency of adverse events e.g. Cesarean section, prolong labour, induction of labour and instrumental delivery in mothers were higher in group M as compared to group N with p value <0.005. Frequency of perinatal mortality, low Apgar score and NICU admission was higher in group M but low birth weight in of group N was higher as compared to group M. Conclusion: According to our findings, gestational diabetes, preterm labour labor, and preeclampsia are more common among obese women. Having a baby with an obese woman might be a risk factor for mother and child. Obesity in mothers increases foetal morbidity and death. Keywords: NICU, C-section, Pre-eclampsia, Mortality, Partum haemorrhage, Low birth weight, Apgar score, Gestational diabetes,